1969
DOI: 10.1002/pssb.19690330228
|View full text |Cite
|
Sign up to set email alerts
|

Die Absorptionskante der Selen–Tellur‐Mischkristallreihe

Abstract: 70,BSowohl dieser Verlauf als auch die sehr stmke Konzentrationsabhangigkeit des Bandabstandes fur kleine Tellurgehalte in Selen geht parallel mit der Variation des Bindungswinkels der Atome in der Mischkristallreihe. Der spektrale Verlauf der Absorptionskonstanten in der Kante entspricht der Theorie fur indirekte ubergange.Solid solutions of selenium and tellurium with a composition varying in steps of 10 atyo were prepared by the Bridgman procedure. The edge absorption of these crystals was investigated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1971
1971
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The fact that near this composition the character of the band gap changes is also shown by optical results. According t o the measurements of Sutter [25], the absorption coefficient at the edge differs appreciably for both polarizations of light for mixtures up to 40% Se content as observed for Te, whereas for higher Se concentrations the difference is much less like for Se. Measurements of the magnetic susceptibility of mixed crystals also indicate that a t about 40% Se content a change in the character of the band gap occurs [261.…”
Section: Intrinsic Conductionmentioning
confidence: 82%
“…The fact that near this composition the character of the band gap changes is also shown by optical results. According t o the measurements of Sutter [25], the absorption coefficient at the edge differs appreciably for both polarizations of light for mixtures up to 40% Se content as observed for Te, whereas for higher Se concentrations the difference is much less like for Se. Measurements of the magnetic susceptibility of mixed crystals also indicate that a t about 40% Se content a change in the character of the band gap occurs [261.…”
Section: Intrinsic Conductionmentioning
confidence: 82%
“…Particularly between the concentrations 0⋅02 and 0⋅2, the variation in the thermal diffusivity is not monotonic whereas there are two maxima. For Sn 1-x Ge x Te such studies are not reported, even though electrical and optical studies are available (Nussbaum 1954;Rosenman 1963;Lanyon 1964;Beyer et al 1969;Sutter 1969;Kessler and Sutter 1971;Dawar et al 1981).…”
Section: Introductionmentioning
confidence: 99%